(untitled) (Fiep Bulletin - online, 2014)
INTRODUCTION: An active physical behavior and a healthy lifestyle are extremely important for the acquisition of a good level of health. Adopting healthy habits can exert strong impact in people’s corporal composition, mainly during adolescence. OBJECTIVE: to gather anthropometric information (about weight and stature) and to identify the lifestyle of Paraguayan adolescents’ with overweight. METHODOLOGY: the study was composed by three girls at the ages of 15 and 16 years old, considered overweight, chosen on purpose, belonging to two groups of a public school of Ciudad Del Este, Paraguay. RESULTS: the adolescents presented high body mass index (BMI); only two of them accomplished 60 minutes of physical activities from moderate to vigorous intensity. The sedentary behavior of the other girl took her more time to do it; just one of the girls presented a risky sedentary behavior to the health. Concerning alimentary habits, it was easy to notice the high consumption of candies, soft drinks and fried food by these adolescents. FINAL CONSIDERATIONS: Despite the fact that only one of the girls presented a low level of physical activities and normal sedentary behavior, the evidences show us that the overweight presented by these youths exists mainly due to the inadequate alimentary habits, for the girls assumed they have much high caloric food (candies, snacks and soft drinks) most of the days of the week